Structural basis of spike RBM-specific human antibodies counteracting broad SARS-CoV-2 variants - Kiyomi Shitaoka; Akifumi Higashiura; Yohei Kawano; Akima Yamamoto; Yoko Mizoguchi; Takao Hashiguchi; Norihisa Nishimichi; Shiyu Huang; Ayano Ito; Shun Ohki; Miyuki Kanda; Tomohiro Taniguchi; et al. (Communications Biology, 2023)
Abstract The decrease of antibody efficacy to mutated SARS-CoV-2 spike RBD explains the breakthrough infections and reinfections by Omicron variants. Here, we analyzed broadly neutralizing antibodies isolated from long-term hospitalized convalescent patients of early SARS-CoV-2 strains. One of the antibodies named NCV2SG48 is highly potent to broad SARS-CoV-2 variants including Omicron BA.1, BA.2, and BA.4/5. To reveal the mode of action, we determined the sequence and crystal structure of the Fab fragment of NCV2SG48 in a complex with spike RBD from the original, Delta, and Omicron BA.1. NCV2SG48 is from a minor VH but the multiple somatic hypermutations contribute to a markedly extended binding interface and hydrogen bonds to interact with conserved residues at the core receptor-binding motif of RBD, which efficiently neutralizes a broad spectrum of variants. Thus, eliciting the RBD-specific B cells to the longitudinal germinal center reaction confers potent immunity to broad SARS-CoV-2 variants emerging one after another.